Analysis of the Effect of Supply Chain Management and Pricing Theory on Excess Return of Stocks - Andre Hernowo; Disman Disman; Ikaputera Waspada; Nugraha Nugraha (International Journal of Supply Chain Management, 2019)
The primary purpose of this study is to compare Capital Asset Pricing Model with Arbitration Pricing Theory by considering the supply chain strategy. Another objective of this study is to determine the effect of Capital Asset Pricing Model (CAPM) and Arbitration Pricing Theory (APT) on excess returns and to determine the best asset pricing model in terms of ability to explain the estimation of excess return. This study examines the effect of variables in asset pricing models and compares the ability of asset pricing models in explaining excess return. The population in this study are Kompas 100 stock for periods 2013 to 2017, and the sampling method of this study is purposive sampling. Then, it is obtained as many as 46 companies selected as research samples. To compare the accuracy between the CAPM model and APT is calculated with R2 or R Square and the Prob. values (F-statistic). Based on the results, the best model that can be used in assessing asset pricing model is Arbitration Pricing Theory, this is evidenced by the value of R2 or R Square of 33.41 % and Prob. (F-statistic) value 0.000000, this value is better than the value of R2 Capital Asset Pricing Model of 2.68% and Prob. (F-statistics) value 0.007354.